“La disputa por las almas. Las órdenes religiosas en Campeche, siglo XVIII”, de Adriana Rocher Salas. - Irigoyen López, Antonio (Naveg@mérica, 2011)
“La disputa por las almas. Las órdenes religiosas en Campeche, siglo XVIII”, de Adriana Rocher Salas.